Tinjauan Pelepasan Informasi Rekam Medis: Studi Kasus Aspek Hukum di RSUP Dr. Hasan Sadikin (RSHS) Bandung - Harie Saktian Yusuf; Imas Masturoh (STIKes Persada Husada Indonesia, 2015)
Security, privacy, secrecy and safety is a device covering the health record data/information, all parties involved in health care should maintain the security of patient’s data/information. Preliminary studies in RSHS showed that there were some problems related those data security such as, the release of medical record information without the written permission or authorization letter from the patient, as much as 660 medical record documents were not returned to the medical records.The purpose of this study are knowing the release of medical record information to the 3rd parties according to the legal regulation in RSUP Dr. Hasan Sadikin Bandung. The research design is qualitative case study. The sampling technique is snowball sampling when the choice of informant based on information from previous informant. Data analysis focused to important findings, classified in decided themes and patterns. The results found that: there was patients's ignorance about the value of medical resumes, users was late to restore the file and brought the file out of the hospital, and insurance was not explaine about informant’s medical record, utilization procedures were not followed, and not used the patient's written consent according to education, research and insurance of BPJS. It was suggested that users should respect to the patient's privacy right, such as obey hospital procedures for patient’s. confidentiality and attach patient’s written consent, and sanctions against the obidient users.